Análise da composição da geleia real por FTIR-ATR e capacidade antioxidante durante ciclos padronizados de descongelamento - Freitas, Camila Natalli Miranda (2020)
Royal jelly (RJ) is a viscous secretion of the hypopharyngeal glands of worker bees and is composed of water, carbohydrates, lipids and proteins, vitamins, riboflavins and minerals. Royal jelly has been studied for its medicinal benefits such as antihypertensive, hepatoprotective, glycemic control, anti-inflammatory and antioxidant effects. The benefits of royal jelly are associated with its composition; therefore, the objective of this work was to verify the effects of standardized thawing cycles on the composition of royal jelly through the analysis of ATR-FTIR and antioxidant capacity in order to mimic the consumption of this natural product in use diary. The results obtained demonstrated that the cycles of thawing of royal jelly caused a decrease in the intensity of the spectra peaks in the ATR-FTIR readings, mainly related to lipids and proteins, and there was also a decrease in the antioxidant capacity of royal jelly in the face of these cycles. This study proved the effectiveness of the ATR-FTIR technique for analyzing the freshness and quality of royal jelly, in addition to demonstrating the effects that short temperature changes over the days, mimicking the daily use by consumers, cause the composition and antioxidant capacity of royal jelly.